The impact of falling oil and gas prices on non-US LNG producers - Henderson, J (Oxford Institute for Energy Studies, 2015)
The fall in the oil price from a high of $115 per barrel in mid-2014 to around $65 per barrel in May 2015 has clearly impacted the revenues and commercial outlook of LNG producers and consumers, given the strong historic link between LNG contract prices and oil. The LNG contract price is generally negotiated in relation to a slope, which captures the link in percentage terms between the oil price in US$ per barrel and the LNG price in US$ per MMBtu. On an energy-equivalent basis, the LNG price would be 17.5 per cent of the oil price, but in order to ensure the competitiveness of gas the slope is normally negotiated within a 13–16 per cent range, depending on the market conditions at the time and the consequent bargaining positions of buyer and seller. A standard assumption is that the average slope is 14.85 per cent (plus a fixed element of $0.5/MMBtu), meaning that at an oil price of $115 the LNG price would be just over $17.50/MMBtu, while at $65 it would fall to around $10.00/MMBtu. LNG contracts generally also include ‘kink points’ which limit the upside and downside for both buyers and sellers (creating what is known as an ‘S curve’), but even with this modification it is obvious that a $50 fall in the oil price will have had a significant impact on LNG suppliers. However, there is a broad range of outcomes across the LNG supply chain due to the differing economics of projects in various countries.